Results of the study of some biochemical values in dog after spaying - Enkhbayar, E; Gereltsetseg, G (Mongolian Journal of Agricultural Sciences, 2015)
It is sometimes necessary to remove gonad of a dog during various age. In order to define the optimal age for spaying (ovariohysterectomy) female dogs, our study objectives were to investigate changes of hormonal and biochemical values in both immature and mature female dogs after spaying. Results of the study on sex hormone levels at different stages of female dog estrous cycle and biochemical values of only mature dogs were presented in this article. Highest progesterone concentration in female puppy occurs during diestrus (20-35 ng/ml), and estradiol level peaked (25-35 pg/ml) during proestrus. In mature dogs for one year after ovariohysterectomy, total proteins in plasma increased by 13.3%, albumin elevated by 31.1%, total lipids by 2.3 times, cholesterol by 3 times and plasma glucose by 2.3 times. Results of the study revealed removal of gonads or ovaries in female dogs leads to greater changes of metabolism, especially lipid or cholesterol metabolism disturbs at highest levels Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 16-21